EFFECT OF THE ADOPTION OF THE CLASSIFICATION OF ACCOUNTING SERVICE ON ACCOUNTING INSTRUCTION. - Himmelblau, David (The Accounting Review, 1931)
Since 1925, John R. Wildnzan as chairman of the Committee on Education, American Institute of Accountants, has endeavored to procure the general adoption of a classification of accounting services. The original report was prepared September 9, 1925. Since then the matter has been discussed at each meeting of the American Institute of Accountants, by the American Society of Certified Public Accountants, the New York Society of Certified Public Accountants and the American Association of University Instructors in Accounting. The classification considered by the 1980 meeting of the American Institute of Accountants is not yet available for publication. The article attempts to discuss the differences between two classifications but the author is very much interested in having a uniform classification of accounting services come into general use. The importance of such a classification of accounting services for instructional purposes in auditing courses will he obvious to any one. From the standpoint of instructing students who expect to become professional auditors, a recognized classification of accountancy services enables the teacher to state definitely that there are certain recognized classes of audit work and point out the objects to be accomplished by each class of audit.